Kontaminasi Dan Distribusi Logam Berat Tembaga (Cu) Dan Zink (Zn) Pada Sedimen Perairan Baturusa, Provinsi Kepulauan Bangka Belitung - Rohman, Jodi; Nugraha, Mohammad Agung; Akhrianti, Irma (Journal of Tropical Marine Science, 2023)
The Baturusa River receives input from various activities ranging from industry, mining, fisheries, large-scale plantations and shipping ports. This research aims to determine the concentration of the heavy metals Copper (Cu) and Zinc (Zn) as well as the status of the level of contamination, contamination and enrichment of the heavy metals copper (Cu) and zinc (Zn) in Baturusa Waters, Bangka Belitung Islands Province. Heavy metal analysis using the AAS method. Concentrations of heavy metals Cu and Zn ranged from 0.73-2.29 mg/kg and ranged from 1.45-14.74 mg/kg. The contamination factor values for heavy metals Cu and Zn are included in the low contamination level (CF<1) with a range of Cu 0.016-0.050 and Zn 0.015-0.155. The results of the I-geo value for Heavy Metal Cu range from -4.881 to -6.530 and for Heavy Metal Zn range from -3.273 to -6.618 which shows that the I-geo value (<0) means it is not contaminated with heavy metals. The PLI value ranges from 0.01-0.08, indicating it is not contaminated. The EF value for the heavy metal Zn is greater than for the heavy metal Cu (Zn>Cu), the value for Cu is 2.32-7.54 and Zn 2.59-11.27. The EF values of the heavy metals Cu and Zn are included in the moderate to sufficient enrichment level category. Variations in EF values in the waters of the Baturusa Estuary, Bangka Belitung Islands Province show that there is input from anthropogenic sources at all stations as well as input from natural weathering processes from land (both physical and chemical).